2015
DOI: 10.1186/s13000-015-0391-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Down-regulated microRNA-124 expression as predictive biomarker and its prognostic significance with clinicopathological features in breast cancer patients

Abstract: BackgroundMicroRNAs (miRNAs) have been documented as playing important roles in cancer development. In this study, we investigated to clarify the clinicopathological significance and prognostic value of miR-124 in breast cancer.MethodsQuantitative Real-time PCR method was used to assess the expression levels of miR-124 in breast cancer patients and the association of miR-124 expression levels with the clinicopathological characteristics in breast cancer patients. Survival and Multivariate Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Second, we only focused on HER-2 positive breast cancer, so further studies are required to validate the association between miR-124 expression, HER2 status, and radioresistance in different cancer subtypes. Interestingly, Arabkheradmand et al (11) reported an association between miR-124 down-regulation and advanced clinical stage and the presence of lymph node metastasis in Iranian patients with breast cancer, however, they found no association between microRNA expression and HER2 status. There are several explanations for the difference between our study and the study by Arabkheradmand et al: 1) The complex relation between miRNA expression and clinic clinicopathological characteristics of the patients might be different in the Iranian and Chinese Han populations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we only focused on HER-2 positive breast cancer, so further studies are required to validate the association between miR-124 expression, HER2 status, and radioresistance in different cancer subtypes. Interestingly, Arabkheradmand et al (11) reported an association between miR-124 down-regulation and advanced clinical stage and the presence of lymph node metastasis in Iranian patients with breast cancer, however, they found no association between microRNA expression and HER2 status. There are several explanations for the difference between our study and the study by Arabkheradmand et al: 1) The complex relation between miRNA expression and clinic clinicopathological characteristics of the patients might be different in the Iranian and Chinese Han populations.…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCC, the epithelial-restricted with serine box/epidermal growth factor receptor (EGFR) and ITGB1 have been reported to be the targets of miR-124 [21, 33]. By a comprehensive search, we found that the 3′-UTR sequence of SphK1 mRNA carries a complementary site for the seed region of miR-124.…”
Section: Discussionmentioning
confidence: 99%
“…As a tumor suppressor, aberrant low expression of miR-124 is often detected in many tumors, such as gynecological, cerebral, and gastric tumors454647. MiR-124 was reported to perform crucial anti-cancer functions in GC4849.…”
Section: Discussionmentioning
confidence: 99%